Impact of drilling in the open pit mining on the environment - Mikić Miomir; Jovanović Milenko; Jovanović Ivana; Petrović Sanja (Mining and Metallurgy Engineering Bor, 2017)
In order to provide better and easier loading of useful component and overburden, the drilling and blasting belong to the important work operations at the open pits. Borehole drilling represents a source of harmful respirable mineral dust beside the applied measures for its prevention at the place of creation. Dust emissions during borehole drilling depends on a method and speed of drilling, borehole diameter, mechanical rock properties and applied method to capture dust in order to suppress the dust concentration in the working and living environment of the open pit.